Qualitative longitudinal research with children and young people - Crivello, G (Springer Singapore, 2015)
There is growing interest in the potential value of qualitative longitudinal research (QLR) for shedding light on temporal dimensions of experience, and on the way personal biographies are shaped by social structures and processes over time. This chapter outlines some of the definitions, designs, advantages and challenges in relation to QLR, focusing on ways of engaging children and young people. It offers three examples of QLR, and describes a selection of methodological tools and techniques for accessing children’s perspectives on their lives, trajectories and social worlds, across time. The chapter underscores the academic and ethical value in involving children in QLR, at the same time bringing to light the complex practical and ethical challenges stemming from their participation.